LANGUAGE LEARNING STRATEGIES EMPLOYED BY EFL LEARNERS IN A RURAL AREA - Yanik Lailinas Sakinah; Putu Dian Danayanti Degeng; Sahiruddin Sahiruddin (Universitas Bengkulu, 2020)
Learning strategy has been widely acknowledged to play an important role in foreign language learning to help the learners in improving language competence. However, studies about language learning in EFL setting in various setting with different participants are still required as to provide a comprehensive representation of how language learning strategies are applied by L2 learners, particularly in an Indonesian EFL setting. This study aimed to examine what language learning strategies are used by EFL learners who work as the local tour guide at National Park of Bromo Tengger Semeru /Taman Nasional Bromo Tengger Semeru (TNBTS), located in East Java, Indonesia. Participants of this study were 33 English learners who work as local tour guide The instruments used was Strategy Inventory for Language Learning (SILL) version 7.0 adapted from Oxford (1990) consisting of 50 questions with 5 scale for each item. This study had a quantitative design as it dealt with the analysis of the numeric data collected from the questionnaire results and employed SPSS software as a tool to analyze descriptive statistics. The result showed that the most frequent strategy used was compensation strategy with mean value 3.64 and the least frequent strategy used was memory strategy with mean value 2.77.